Recognizing and managing on toxicities in cancer immunotherapy - Liu Yang; Huifang Yu; Shuang Dong; Yi Zhong; Sheng Hu (Tumor Biology, 2017)
Over the past 4 years, cancer immunotherapy has significantly prolonged survival time of patients with prostate cancer, melanoma, lung cancer, and liver cancer, but its side effects are also impressive. Different types of the immune therapeutic agents have different on-target or off-target toxicity due to high affinity or weak specificity, respectively. Treatment toxicity spectrums vary greatly even in patients with the same type of cancer. Common toxicities are fevers, chills, diarrhea colitis, maculopapular rash, hepatitis, and hormone gland disorder; therefore, routine monitoring of thyroid function, liver function, renal function, and complete blood count are absolutely necessary once treatment begins. Some side effects are reversible, and can be processed through the standard medicines. However, serious toxicities are lethal, which should be frequently followed-up, identified at an early stage and immediately symptomatic treated by high-dose immunosuppressors. In this case, thereafter, the same agent should not be challenged again.